2015
DOI: 10.1371/journal.pone.0135204
|View full text |Cite
|
Sign up to set email alerts
|

Disentangling Membrane Dynamics and Cell Migration; Differential Influences of F-actin and Cell-Matrix Adhesions

Abstract: Cell migration is heavily interconnected with plasma membrane protrusion and retraction (collectively termed “membrane dynamics”). This makes it difficult to distinguish regulatory mechanisms that differentially influence migration and membrane dynamics. Yet such distinctions may be valuable given evidence that cancer cell invasion in 3D may be better predicted by 2D membrane dynamics than by 2D cell migration, implying a degree of functional independence between these processes. Here, we applied multi-scale s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 43 publications
0
25
0
Order By: Relevance
“…Cell migration is the product of membrane dynamics that can be divided into protrusive and retractive processes ( Ridley, 2003 ). We quantitatively compared the spatial and temporal dynamics of membrane protrusions and retractions between and within each migration mode based on defining membrane dynamics over the minimal imaging interval of 5 min ( Figure 2 ) ( Kowalewski et al, 2015 ). This revealed that protrusions share similar size (area) distributions in both modes ( Figure 2A ), while retraction events are more extreme in size during Discontinuous migration, that is, more frequently very small or very large ( Figure 2B ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cell migration is the product of membrane dynamics that can be divided into protrusive and retractive processes ( Ridley, 2003 ). We quantitatively compared the spatial and temporal dynamics of membrane protrusions and retractions between and within each migration mode based on defining membrane dynamics over the minimal imaging interval of 5 min ( Figure 2 ) ( Kowalewski et al, 2015 ). This revealed that protrusions share similar size (area) distributions in both modes ( Figure 2A ), while retraction events are more extreme in size during Discontinuous migration, that is, more frequently very small or very large ( Figure 2B ).…”
Section: Resultsmentioning
confidence: 99%
“…This facilitates the leveraging of natural or induced heterogeneity to define: i) the statistical structure of variation (e.g. progressive or discrete) within and between cell populations, as well as; ii) key trends, dependencies and relationships within the cell migration system ( Lock et al, 2014 ; Keren et al, 2008 ; Kiss et al, 2015 ; Kowalewski et al, 2015 ; Ku et al, 2012 ; Lee et al, 2015 ; Lock and Strömblad, 2010 ). Here, we extend on this approach by employing a tailored analytical toolbox to detect two quantitatively distinct sub-modalities of mesenchymal migration, thus illuminating the discrete nature of variation within this general migration archetype.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, these analyses both confirmed and explained the visual impressions that originally differentiated Discontinuous from Continuous migration. In addition, given the strong correspondence between retraction (but not protrusion) size and cell speed, these analyses now add migration mode and cell speed to motility initiation as aspects of migration where membrane retraction appears to be the deterministic membrane process (Barnhart et al, 2015;Kowalewski et al, 2015;Cramer, 2010). correlation values from the Discontinuous to the Continuous mode.…”
Section: Discussionmentioning
confidence: 99%
“…This facilitates the leveraging of natural or induced heterogeneity to define: i) the statistical structure of variation (e.g. progressive or discrete) within and between cell populations, as well as; ii) key trends, dependencies and relationships within the cell migration system (Lock et al, 2014;Keren et al, 2008;Kiss et al, 2015;Kowalewski et al, 2015;Ku et al, 2012;Lee et al, 2015;Lock and Strö mblad, 2010). Here, we extend on this approach by employing a tailored analytical toolbox to detect two quantitatively distinct sub-modalities of mesenchymal migration, thus illuminating the discrete nature of variation within this general migration archetype.…”
Section: Introductionmentioning
confidence: 99%
“…Patch Morphology Analysis Dynamic software (Digital Cell Imaging Laboratories, Belgium) was used for analysis of static (fixed) and dynamic (live) cell imaging data, except where otherwise specified. Analysis strategy and parameterisation are as described previously (Hernández-Varas et al, 2015;Kiss et al, 2015;Kowalewski et al, 2015;Lock et al, 2014;Shafqat-Abbasi et al, 2016). Briefly, both cells and intracellular adhesion cohorts were segmented according to pixel intensity gradient analysis.…”
Section: Image Analysismentioning
confidence: 99%